3rd European Quality of Life Survey Quality of life in Europe : Social inequalities - Suh, Ellie; Tsang, Tiffany; Vizard, Polly; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2013)
This report uses data from the European Quality of Life Survey (EQLS) to examine social inequalities in quality of life in the European Union. Four critical domains of life are examined: health, standard of living, productive and valued activities, and individual, family and social life. Variation in these four domains is measured by gender, age, disability status, employment status and citizenship status. The role of other important drivers of social inequalities such as educational status, occupational group, urbanisation, gross domestic product (GDP) per capita, income, welfare regime and healthcare system is also discussed. The results of the third EQLS (2011) are compared with those of the second EQLS (2007) to assess the impact of the economic crisis on social inequalities and on the disadvantages experienced by population subgroups in Europe.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Social surveys -- European Union countries; Quality of life -- European Union countries; Europe -- Social conditions -- 21th century; Electronic books